PENGARUH STORE ATMOSPHERE DAN STORE LOCATION TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA KAWAN SEDUH COFFER SURABAYA - Praditya, Dhemas Arya Praditya; Kaihatu, Thomas Stefanus (PERFORMA, 2023)
The aim of this research is to conduct an analysis of the influence of store atmosphere and store location on customer loyalty with customer satisfaction as a mediating variable which was carried out at Kawan Seduh Coffee Surabaya. All tests were carried out using the Partial Least Aquare (PLS) research method using SmartPLS software as the analytical tool used. This research involved 140 respondents with the criteria being respondents who had made purchases more than twice. Based on the research results, it was found that store atmosphere has a significant effect on customer loyalty and satisfaction, store location has a significant effect on customer satisfaction and has no effect on customer loyalty, customer satisfaction has a significant effect on customer loyalty and can mediate the effect of store atmosphere on customer loyalty, but cannot mediating the influence of store location on Kawan Seduh Coffee customer loyalty